Priorização de remanescentes florestais visando a conservação da biodiversidade - Toro, Ana (Universidade Federal de São Carlos, 2019)
The Atlantic forest fragmentation is considered a serious threat for biodiversity since this biome is considered one of the hottest hotspots. Due to this reason, there are many environmental strategies being developed to support its conservation. In this sense, the main objective of this study was the developing of a patches prioritization index (PPI), in order to support conservation actions and researches. For that, we firstly performed a forest remnants diagnosis in the study area through the set of landscape ecology metrics. The metrics AREA, SHAPE and NEARD were selected to compose PPI, considering their importance to forest conservation, according to the literature and experts. The three metrics were normalized to the scale varying from 0 to 1, that was the same used by the index. So, we calculated the PPI value for the forest patches, that were divided into priority classes (low to high), supporting the definition of priority regions for biodiversity conservation in the landscape. Finally, using a rapid ecological assessment (BII), the PPI was validated in the field. According to the Index, patches large, connected, and characterized by regular shape, are the priority for biodiversity conservation. On the other hand, patches with an irregular shape, isolated and small, received a low level of priority for biodiversity conservation. In this context, we concluded that the PPI index is adequate for patches prioritization aiming at biodiversity conservation. Thus, PPI could be used for the decision-making process in the prioritization of patches and regions for biodiversity conservation.
Keywords: Mata atlântica; Priorização de remanescentes; Métricas de ecologia da paisagem; Diagnóstico de fragmentos florestais; Atlantic forest; Prioritization of forest remnants; Landscape ecology metrics; forest patches diagnosis; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::CONSERVACAO DE AREAS SILVESTRES